Extended Use of The Spanner® Temporary Prostatic Stent in Catheter-Dependent Men with Comorbidities - Angelo J. Cambio; Richard M. Roach; Paul Arnold; Joseph Cambio; Clifford D. Gluck; Sean P. Heron (Advances in Urology)
Purpose. This US FDA investigational device exemption (IDE) study evaluated the extended use of The Spanner® Temporary Prostatic Stent in catheter-dependent men with urinary retention who were not deemed candidates for corrective surgery but demonstrated bladder contractility. Materials and Methods. The Spanner was placed for 3 cycles of 30 days in catheter-dependent men with comorbid conditions, confirmed detrusor contractility, and catheter-associated discomfort. At each visit, postvoid residual, maximum flow rate, international prostate symptom score, quality of life, and adverse events were assessed. Voiding success was defined as PVR ≤ 150 ml at all visits. Results. One hundred seven men were enrolled at 8 US sites; 82/107 (76.6%) completed the trial, and 79/107 (73.8%) successfully maintained PVR ≤ 150 ml for the trial duration. Patients were 77.1 ± 10.6 years old; 63/107 (58.9%) were dependent on Foley and 40/107 (37.4%) on intermittent catheterization for 36.0 ± 39.3 days and 30.2 ± 45.8 days, respectively. 25/107 (23.4%) discontinuations were primarily due to voluntary patient withdrawal 9/107 (8.4%), investigator-initiated withdrawal 8/107 (7.5%), or lack of effectiveness 4/107 (3.7%). During Spanner use, the mean Qmax was 11.2 ± 6.6, mean IPSS was 7.5 ± 6.4, and mean QOL was 2.0 ± 1.6. The most prevalent device-related adverse events were asymptomatic bacteriuria 25/107 (23.4%), discomfort 10/107 (9.4%), and urinary urgency 8/107 (7.5%). No device-related serious AEs were reported. Conclusions. This study demonstrates that catheter-dependent men with sufficient bladder contractility can achieve volitional voiding and successful bladder drainage using The Spanner Temporary Prostatic Stent for extended periods of time.